Unraveling the role of cell wall remodeling factors in Arabidopsis root development - Ramakrishna, Priya (2017)
Lateral roots are a key component of the plant root system architecture that help anchorage in soil and acquisition of water and nutrients. In the dicot Arabidopsis, lateral roots initiate post-embryonically from a specialised set of cells at the xylem pole of the pericycle cell layer termed ‘founder cells (FC)’, overlaid by three distinct tissue layers – endodermis, cortex, epidermis. The FCs undergo a coordinated series of asymmetric cell divisions (ACD) to form a primordium that grows and emerges through these overlying layers as a mature lateral root. Different auxin signaling modules, as well as tight regulation of the cell geometry are important during early organogenesis. In this study, we were interested to identify molecular components that influence cell wall remodeling properties and cell geometry in the FC and regulates asymmetric cell division during early lateral root initiation. Transcriptomic analysis of FCs (De Smet et al., 2008) identified a candidate gene EXPANSINA1 (EXPA1) of expansin superfamily, known for their unique ability to alter linkage between the cell wall polymers and cause wall loosening. In vivo expression studies showed that EXPA1 is expressed in FCs prior asymmetric cell division. The mutant expa1-1 exhibits perturbed ACD with a delay in kinetics of primordia from Stage I to II, loss in radial expansion of FCs in response to auxin which is important for organised formative divisions. To understand if these defects are due to altered properties of the cell wall, and role of auxin in this process, we developed an optimised technique to study the chemical properties of the FC cell wall junctions based on confocal Raman spectroscopy. This showed altered interactions in expa1-1 between the major cell wall polymers xyloglucans and pectins locally in the pericycle cell wall upon auxin treatment, that could influence cell geometry during early lateral root development. Additionally, sugar monomer analysis of digested whole roots showed interesting alterations in representative global wall sugar levels in the root which although diluted due to lack of tissue specificity warrants further study. In conclusion, the combination of molecular and biochemical analyses reveals that auxin dependent regulation of EXPA1 plays an important role in lateral root FC and is required for organised asymmetric cell division.